1998
DOI: 10.1038/bjc.1998.659
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality in relation to monitoring for radionuclide exposure in three UK nuclear industry workforces

Abstract: Summary Cancer mortality in 40 761 employees of three UK nuclear industry facilities who had been monitored for extemal radiation exposure was examined according to whether they had also been monitored for possible intemal exposure to tritium, plutonium or other radionuclides (uranium, polonium, actinium or other unspecified). Death rates from cancer were compared both with national rates and with rates in radiation workers not monitored for exposure to any radionuclides. Among workers monitored for tritium ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 19 publications
(32 reference statements)
1
42
0
1
Order By: Relevance
“…Compared with the former group, there were excesses of deaths from cancers of the pleura, breast, and ill-defined and secondary sites, but for none of these sites was there evidence that risk was associated with cumulative dose. Because of the indications from a parallel study of an association between the time since first monitoring for plutonium and the risk of deaths from all malignant neoplasms considered (Carpenter et al, 1998), we repeated those analyses using our data for the Sellafield workforce. Comparing plutonium workers with other radiation workers, the ratio of the death rates in the two groups in the periods <10 years, 10Ð19 years and ³20 years since monitoring started were 0.82, 1.03 and 1.12.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the former group, there were excesses of deaths from cancers of the pleura, breast, and ill-defined and secondary sites, but for none of these sites was there evidence that risk was associated with cumulative dose. Because of the indications from a parallel study of an association between the time since first monitoring for plutonium and the risk of deaths from all malignant neoplasms considered (Carpenter et al, 1998), we repeated those analyses using our data for the Sellafield workforce. Comparing plutonium workers with other radiation workers, the ratio of the death rates in the two groups in the periods <10 years, 10Ð19 years and ³20 years since monitoring started were 0.82, 1.03 and 1.12.…”
Section: Discussionmentioning
confidence: 99%
“…No significant associations were reported in Sellafield, Atomic Weapons Establishment, Hanford, Japanese, or combined US, UK and Canadian cohorts. [305][306][307][308][309][310][311][312] Furthermore, there were no trends in NHL risk based on cumulative radiation dose in these cohorts. Other studies have reported no significant associations among US military personnel who participated in atmospheric nuclear weapons tests, 313 participants in the UK atmospheric nuclear weapons tests, 314 residents living near nuclear installations, 315,316 uranium miners, 317 dental workers 318 or cohort members of the National Dose Registry of Canada.…”
Section: Radiation Exposurementioning
confidence: 99%
“…Carpenter et al (1998) examined a large cohort of British nuclear industry workers who had been monitored for internal exposures and found that certain patterns of monitoring may be associated with particular cancers; however, the measures of exposure were relatively crude. Omar et al (1999) studied the group of workers exposed to plutonium at the Sellafield nuclear installation in Britain for whom assessed organ-specific doses due to plutonium were available, and concluded that the plutonium workers were not at an increased risk of cancer when compared with other radiation workers.…”
Section: Introductionmentioning
confidence: 99%